2019
DOI: 10.1139/cjce-2018-0334
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of PCM-incorporated normal and lightweight concretes containing silica fume

Abstract: Improving the thermal performance of concrete, as an important construction and pavement material, by incorporating phase change materials (PCMs) has been the topic of much research. Also, various carrier agents such as lightweight aggregate (LWA) have been introduced to incorporate PCMs into concrete. However, incorporation of PCM-impregnated LWA reduces the compressive strength of concrete. In this study, the application of silica fume to improve the compressive strength of PCM-incorporated concrete is inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, certain recent attempts, such as the coating of PCM containing LWA, the use of nanomaterials in PCMs, pipes filled with PCM, the use of supplementary cementitious materials in concrete to overcome the degradation effect of PCM, and PCM impregnation into concrete pores from the surface, all show performance improvements of PCM-containing concrete [ 91 , 148 , 149 ]. Jafarabad et al [ 28 ] reported that the compressive strength was improved by 25% by using the silica fume in a cement matrix and polyethylene glycol as a PCM compared to a specimen without silica fume. Le et al [ 150 ] revealed that the coating on PCM containing LWA with cement is an efficient method to improve the performance of concrete.…”
Section: Techniques For the Safe Deposit Of Pcm In Concrete For Large-scale Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, certain recent attempts, such as the coating of PCM containing LWA, the use of nanomaterials in PCMs, pipes filled with PCM, the use of supplementary cementitious materials in concrete to overcome the degradation effect of PCM, and PCM impregnation into concrete pores from the surface, all show performance improvements of PCM-containing concrete [ 91 , 148 , 149 ]. Jafarabad et al [ 28 ] reported that the compressive strength was improved by 25% by using the silica fume in a cement matrix and polyethylene glycol as a PCM compared to a specimen without silica fume. Le et al [ 150 ] revealed that the coating on PCM containing LWA with cement is an efficient method to improve the performance of concrete.…”
Section: Techniques For the Safe Deposit Of Pcm In Concrete For Large-scale Applicationsmentioning
confidence: 99%
“…Accordingly, different techniques of PCM inclusion in building materials, such as alveolar bricks, hollow bricks and CSM panels, have been tested [ 27 ]. Therefore, different non-contact incorporation methods of PCM with concrete are attracting much attention among sustainable building researchers [ 28 , 29 ]. Eventually, PCM incorporation in construction materials will support the UN SDGs, but no attempts have been made to correlate the contributions of PCM concrete composites to realize the UN SDGs.…”
Section: Introductionmentioning
confidence: 99%